The impact of the professional education program for in-service teachers on pedagogical competence in Indonesia - Am, St. Asriati; Am, St. Asmayanti; AM, Sitti. Asnaeni; Saiful, Saiful (LPMPP Universitas Negeri Yogyakarta, 2026)
The Teacher Professional Education Program (PEP) is a government-initiated in-service training scheme intended to strengthen Indonesian teachers’ professional, social, personal, and pedagogical competence. This study describes the pedagogical competence of in-service English as a Foreign Language (EFL) teachers who have completed PEP. A descriptive survey was conducted with 47 in-service EFL teachers who attended PEP at Universitas Muhammadiyah Makassar in the 2020–2021 academic year, selected through purposive sampling. Teachers’ pedagogical competence was measured using a Likert-scale questionnaire that covered six components: use of learning media, understanding students’ characteristics, pedagogical knowledge, interactive teaching methods, lesson planning, and assessment practices. Descriptive analysis of the questionnaire responses shows that participants generally report high levels of pedagogical competence across these components, particularly in planning lessons and conducting assessment, while some aspects, such as the consistent use of technology and English in the classroom, remain less strong. These findings portray the pedagogical profile of PEP graduates and suggest that structured professional education programs can support the ongoing development of in-service EFL teachers in the Indonesian context.